Reconciling the Original Schumpeterian Model with the Observed Inverted-U Relationship between Competition and Innovation - Roberto Bonfatti; Luis A. Bryce Campodonico; Luigi Pisano (Center for Economic Studies and ifo Institute (CESifo), 2018)
Empirical studies have uncovered an inverted-U relationship between product-market competition and innovation. This is inconsistent with the original Schumpeterian Model, where greater competition reduces the profitability of innovation. We show that the model can predict the inverted-U if the innovators' talent is heterogenous, and privately observable. With competition low and profitability high, talented innovators are credit constrained, since others are eager to mimic them. As competition increases, the mimickers become less eager, and talented innovators can invest more. This generates the increasing part of the relationship. With competition high, talented innovators are unconstrained, and the relationship is decreasing.
Keywords: O38; E60; G38; 330; innovation; competition; Schumpeterian Model of Growth; asymmetric information